UPAYA PENINGKATAN PERFORMA PLANT A DI PT X - Thea Callista Setiawan; Felecia - (Jurnal Titra, 2014)
Plant A’s performance is measured by KPI (Key Performa Indicator) which some of them didn’t meet the target. The focus improvement is LU-15 which the KPI 2013 shows the uptime’s achievement 22.75 of 40% and CPQI 113 of 112 pts. The average achievement of early 2014 until week 6 for uptime 20.80% of 40% while CPQI 126,75 pts of 110 pts. This shows the performance is still far from target. OPI focus on uptime is brand change, inner liner, and stamp tax while for CPQI are POV(water content) and CTW.  Repairs completed through QCC (Quality Control Circle) use PDCA (Plan, Do, Check, Action) concept which leads the team to breakdown the problem, determine the action plan, implementation, evaluation and standardization. Standardization has been implemented for machine, process and focus team improvement. Average achievement after repairs up to week 19 for uptime reach 24.43 of 40%. The achievement has not meets the target because of many variables that influence such as damage of the machine, but overall the performance had increased. Average CPQI reach 116 of 110 pts where in the last 5 weeks has been decreased and reach the target, but still need consistency to stabilization performance.